Performance Analyses of PV Panel for Istanbul - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2009)
Renewable energy sources such as photovoltaic energy are considered promising in order to meet the continuously increasing demand for energy in the world. These sources have very attractive features. Clean and renewable energy production is getting more attractive due to global warming, environmental factors and decrease in conventional energy sources. Photovoltaic cells will be a good alternative against the conventional energy sources in the near future, with their decreasing costs and increasing efficiencies. Besides these benefits of photovoltaic systems they need to effective design before installing systems. In this study stand alone PV performance is tested experimentally for Istanbul-Goztepe.
Keywords: Photovoltaic System; DC Loads; Energy Consumption; Meteorological Conditions